Pharmacogenomic profiling of variants affecting efficacy and toxicity of anti-infective medicines in a south Asian population from Sri Lanka - Priyanga Ranasinghe; Hajanthy Jeyapragasam; Nirmala Sirisena; D. P. Bhagya Hendalage; Vajira H. W. Dissanayake (BMC Infectious Diseases)
Abstract Background Anti-infective medicines are crucial for treating infections, but improper dosing can cause toxicity, resistance and treatment failure. Pharmacogenomics can address genetic variations affecting drug efficacy and safety. Despite the high burden of diseases like TB and HIV in Sri Lanka and South Asia, pharmacogenomic data for these populations are limited. This study aims to fill this gap by investigating pharmacogenomic variants in a South Asian population from Sri Lankan. Methods Pharmacogenomic data on anti-infective medicines were obtained from the PharmGKB database, selecting variants with evidence levels 1 A, 1B, 2 A, and 2B. Sri Lankan genetic data were sourced from an anonymized database of 670 Sri Lankans maintained by the Centre for Genetics and Genomics, Faculty of Medicine, University of Colombo. MAFs were compared between Sri Lankan sub-populations and global data from gnomAD, with statistical significance set at p < 0.05. Results MAFs of NAT2 gene rs1041983 and rs1799931 variants were, 43.7% (95%CI:41.1–46.4), 7.3% (95%CI:6.0-8.8), respectively. The UGT1A1 rs4148323 variant had a MAF of 3.5% (95%CI:2.6–4.6). In the CYP2B6 gene, 109 individuals were homozygous for the rs3745274 (poor metaboliser) variant, with a MAF of 39.6% (95%CI:37.0-42.3), while the rs34097093 and rs28399499 variants had no individuals homozygous for the variant (MAF: 0.2% [95%CI:0-0.5] (poor/intermediate metaboliser), and 0.1% [95%CI:0-0.4] (poor/intermediate metaboliser), respectively). The MAFs of the CYP2C19 rs12769205 (poor/intermediate metaboliser), rs4244285 (poor/intermediate metaboliser), rs3758581 (poor/intermediate metaboliser), and rs4986893 (poor/intermediate metaboliser) variants were 41.9% (95%CI:39.3–44.6), 41.9% (95%CI:39.2–44.7), 9.7% (95%CI:8.2–11.4), and 0.5% [(95%CI:0.2–1.1), respectively. Most variants showed significant differences compared to global populations, with some exhibiting higher frequencies, particularly when compared to Europeans. CYP2C19 rs12769205 and rs4244285 exhibited higher MAFs in Sri Lankans compared to both other South Asians and Europeans. The NAT2 rs1041983, NAT2 rs1799931, CYP2C19 rs4986893, CYP2C19 rs3758581, and CYP2B6 rs3745274 variants demonstrated significantly higher MAFs than in Europeans but not significantly different from South Asians. Conclusion This preliminary study identifies variants in NAT2, UGT1A1, CYP2B6, and CYP2C19 genes relevant to the metabolism of anti-TB drugs, antiretrovirals, and voriconazole among Sri Lankans. Several variants, including CYP2C19 rs12769205 and rs4244285, showed higher MAFs, particularly in comparison to European populations, indicating potential differences in drug response. However, the nature of the study limits the ability to explore clinical correlations with the genotypes, therefore further research focusing on clinical correlation and functional validation is required.